2020
DOI: 10.1038/s41598-020-77143-6
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine receptor D1- and D2-agonists do not spark brown adipose tissue thermogenesis in mice

Abstract: Brown adipose tissue (BAT) thermogenesis is considered a potential target for treatment of obesity and diabetes. In vitro data suggest dopamine receptor signaling as a promising approach; however, the biological relevance of dopamine receptors in the direct activation of BAT thermogenesis in vivo remains unclear. We investigated BAT thermogenesis in vivo in mice using peripheral administration of D1-agonist SKF38393 or D2-agonist Sumanirole, infrared thermography, and in-depth molecular analyses of potential t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 61 publications
0
3
0
Order By: Relevance
“…It is a key neurotransmitter in the hypothalamus and pituitary and secreted by specific neurons in a certain part of the brain ( 96 ). The DA receptor is a member of the G protein-coupled receptor family ( 97 , 98 ), which is divided into two families: D1-like receptors (D1 and D5) and D2-like receptors (D2, D3, and D4) ( 99 , 100 ). L-741626, a dopamine D2-like receptor antagonist, is expressed in airway smooth muscle and can relax ASM, which further indicates that dopamine D2-like receptor induces bronchiectasis by activating the intracellular cAMP signal pathway ( 101 ), while some researchers noticed that SCH23390, a dopamine D1-like receptor antagonist, had a contractile effect on the trachea and then found that there were DRD1 receptors in rat airway smooth muscle, which regulated tracheal relaxation through the cAMP signaling pathway ( 102 , 103 ).…”
Section: Hormones Act As Messengers In the Treatment Of Asthma With Tcmmentioning
confidence: 99%
“…It is a key neurotransmitter in the hypothalamus and pituitary and secreted by specific neurons in a certain part of the brain ( 96 ). The DA receptor is a member of the G protein-coupled receptor family ( 97 , 98 ), which is divided into two families: D1-like receptors (D1 and D5) and D2-like receptors (D2, D3, and D4) ( 99 , 100 ). L-741626, a dopamine D2-like receptor antagonist, is expressed in airway smooth muscle and can relax ASM, which further indicates that dopamine D2-like receptor induces bronchiectasis by activating the intracellular cAMP signal pathway ( 101 ), while some researchers noticed that SCH23390, a dopamine D1-like receptor antagonist, had a contractile effect on the trachea and then found that there were DRD1 receptors in rat airway smooth muscle, which regulated tracheal relaxation through the cAMP signaling pathway ( 102 , 103 ).…”
Section: Hormones Act As Messengers In the Treatment Of Asthma With Tcmmentioning
confidence: 99%
“…The expression of dopamine receptors in adipose tissue has been confirmed in both rodents and humans [ 15 , 16 ], and some dopamine actions have been studied [ 16 19 ]. However, the current knowledge of dopaminergic signaling in human adipose tissue in the context of obesity and T2D and its direct implications in adipose tissue metabolism is limited.…”
Section: Introductionmentioning
confidence: 99%
“…D1-like receptors in brown adipocytes increase oxygen consumption rates and mitochondrial mass through p38 MAPK phosphorylation [ 96 ]. Nevertheless, the relevance of the effect of DA and its receptors on brown adipose tissue is still controversial, since the acute peripheral administration of a D1-like receptor agonist SKF38393 in mice only transiently increased brown tissue temperature after injection, while there was no sustained difference in temperature after repeated daily administration [ 97 ]. Moreover, these effects could be attributed to indirect consequences of DA receptors activation in the vascular system via peripheral action during administration of DA receptor agonists [ 98 ].…”
Section: Introductionmentioning
confidence: 99%